2018
DOI: 10.5194/bg-15-6067-2018
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting biosphere responses to hydrometeorological extremes: revisiting the 2010 western Russian heatwave

Abstract: Abstract. Combined droughts and heatwaves are among those compound extreme events that induce severe impacts on the terrestrial biosphere and human health. A record breaking hot and dry compound event hit western Russia in summer 2010 (Russian heatwave, RHW). Events of this kind are relevant from a hydrometeorological perspective, but are also interesting from a biospheric point of view because of their impacts on ecosystems, e.g., reductions in the terrestrial carbon storage. Integrating both perspectives mig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 64 publications
6
51
0
Order By: Relevance
“…It has been shown that despite the local dominance, water-related NEE anomalies largely cancel spatially in RS+METEO and TRENDY, resulting in the dominance of temperature-related NEE anomalies in globally integrated land sink IAV , but see Humphrey et al, 2018, for a different perspective). Studies on effects of water availability on spatial GPP anomalies using the RS data yielded highly plausible patterns that were consistent with independent data (Flach et al, 2018;Orth et al, 2019;Walther Figure 7. Mean seasonal variations in net land carbon release for the period 2008-2010 over TRANSCOM regions.…”
Section: Interannual Variability Of Net Ecosystem Exchangesupporting
confidence: 74%
See 3 more Smart Citations
“…It has been shown that despite the local dominance, water-related NEE anomalies largely cancel spatially in RS+METEO and TRENDY, resulting in the dominance of temperature-related NEE anomalies in globally integrated land sink IAV , but see Humphrey et al, 2018, for a different perspective). Studies on effects of water availability on spatial GPP anomalies using the RS data yielded highly plausible patterns that were consistent with independent data (Flach et al, 2018;Orth et al, 2019;Walther Figure 7. Mean seasonal variations in net land carbon release for the period 2008-2010 over TRANSCOM regions.…”
Section: Interannual Variability Of Net Ecosystem Exchangesupporting
confidence: 74%
“…Nevertheless, various studies have shown that SIF is currently the best proxy for photosynthesis that can be remotely sensed directly, in particular at seasonal timescale, and over regions with strong seasonal cycles. This is supported by strong empirical relationships between GPP and SIF across different satellites and retrieval methods as well as from EC data, crop inventories and datadriven GPP methods (Frankenberg et al, 2011;Guanter et al, 2014;Joiner et al, 2018;Sun et al, 2017;Walther et al, 2016). This gives us confidence in using SIF as an independent data stream for photosynthesis to evaluate FLUXCOM products.…”
Section: Rationale Of Gpp-sif Comparisonmentioning
confidence: 71%
See 2 more Smart Citations
“…compound dry and hot events) (Seneviratne et al 2012, Leonard et al 2014, Liu et al 2017, Miralles et al 2018. Recent decades have witnessed multiple compound dry and hot events in different regions, such as Europe (2003), China (2006), Russia (2010), southern US (2011), and southern Africa (2015-2016) (Barriopedro et al 2011, Hoerling et al 2013, Flach et al 2018, Herring et al 2018, Wu et al 2019. The compound dry and hot event may lead to impacts larger than the sum of impacts from individual extremes and has attracted increased attention in recent decades (Seneviratne et al 2012, Kopp et al 2017.…”
Section: Introductionmentioning
confidence: 99%